Coral Reefs of North East Pulau Langkawi - Y. A, Affendi (Malaysian Journal of Science, 2005)
The coral reefs of north east Pulau Langkawi was studied in the month of April 2004 to assess their present status. Five of the best sites according to their percentage of live coral cover were selected. Using SCUBA and a modified Reef Check method the sites were surveyed and the percentage of live coral cover was found to be ranging from 26.7-58.3%. Various coral growth forms and even giant clams were observed. The study also added a new record to the coral reef map of north east Pulau Langkawi.